Líquen escleroso vulvar: fotobiomodulação e terapia fotodinâmica como alternativas à corticoterapia - Belotto, Renata Aparecida (2015)
Vulvar Lichen Sclerosus (VLS) is a chronic lymphocyte mediated dermatosis with unclear etiopathogenesis and difficult clinical control besides the risk of malignant transformation to squamous cell carcinoma of the vulva. The treatment is based on topical steroids that can cause undesirable side effects, however photonic therapies have been described in autoimmune diseases of the skin which encouraged this study. There were evaluated twenty eight women with histological diagnosis of VLS distributed into three groups: Photodynamic Therapy (PDT), Low Intensity Laser Therapy (LILT) and Topical Steroids and the objective was to compare the clinical effects before and after treatment by measuring pruritus, skin thickness, lesion area and temperature. No significant difference was observed in the intensity of pruritus between the groups. The Steroid therapy group showed significant variation in the longitudinal thickness of the skin in relation to LILT group (p = 0.000) with a reduction of -8.48%, while in LILT increased 24.8% as well as the PDT group with 20.9 %. However the variation of the transverse thickness was not different between the groups. The change in the lesion area showed no difference between groups. The LILT group showed significant temperature increase (3.03%) compared to PDT (-2.29%) and steroid (-1.45%) (p = 0.002) groups. Recurrences were registered in the corticosteroid group in two months, PDT in one and LILT in four months post treatment. The results showed that photonic therapies may be considered as treatment for VLS.